2006
DOI: 10.1111/j.1939-1676.2006.tb02911.x
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Protein Electrophoresis of 100 Paired Canine Cerebrospinal Fluid and Serum

Abstract: This study was performed to investigate the diagnostic relevance of cerebrospinal fluid (CSF) high resolution electrophoresis. The laboratory technique was applied to 100 paired samples of canine CSF and serum, with paired samples tested during the same analytical run, as recommended in human medicine. Ninety four of the dogs had a neurological disease and 6 healthy dogs served as a control group. A strong linear correlation between CSF total protein concentration and the albumin quota (AQ) was found in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…In this study, an increased gamma globulin ratio and elevated albumin levels were observed in the CSF of all dogs with EAE. In addition, patterns of the CSF albumin and gamma globulin ratio increases were similar to that observed in cases of canine autoimmune encephalitis [ 2 ].…”
Section: Discussionsupporting
confidence: 62%
“…In this study, an increased gamma globulin ratio and elevated albumin levels were observed in the CSF of all dogs with EAE. In addition, patterns of the CSF albumin and gamma globulin ratio increases were similar to that observed in cases of canine autoimmune encephalitis [ 2 ].…”
Section: Discussionsupporting
confidence: 62%
“…Each dog presented a type 1 protein electrophoresis profile consistent with those previously described in healthy dogs (Behr et al, 2006) (Fig. 2).…”
Section: Csf Albumin Concentration and Qalbsupporting
confidence: 55%
“…Electrophoresis profiles with low albumin concentrations are frequently non-interpretable (Behr et al, 2006). Thanks to the microconcentration step we used, all electrophoresis profiles were interpretable even for albumin concentrations <20 mg/dL.…”
Section: Tablementioning
confidence: 99%
“…22 Recently, high-resolution electrophoresis (HRE) has been proposed as an electrophoretic technique to be applied to fluids with low concentration of proteins such as urine or cerebrospinal fluid. 2,3,8,9,12,21 HRE is a zonal electrophoresis in which proteins migrate based on charge, volume, and mass. HRE differs from the standard AGE (the technique routinely used in serum) by the use of a more alkaline buffer (pH 8.6 vs. 8.5), a different barbital content (0.18% vs. 0.61%), and a different voltage per hour (40 V/hr vs. 36 V/hr) at 20°C.…”
Section: Introductionmentioning
confidence: 99%